Research and Teaching in Small Business Finance: A Note on Resources - Richard G. P. McMahon (Journal of Small Business Finance, 1993)
In an emerging field of scholarship such as Small Business Finance, there is often a chicken-and-egg problem at the outset. Prospective researchers are generally discouraged by an initial lack of infrastructure such as relevant bibliographic facilities, journals, conferences and data sources. In the interests of conserving resources, the following details of research and teaching resources developed at or through the School of Accounting, Finance, and Management at The Flinders University of South Australia are made available.
Keywords: G30; M21; A20; 650; Small Business; Finance; Teaching